Dinamika Komunikasi Pendidikan pada Era Disrupsi - Rahmad Rahmad (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Progress of the era, also known as the era of disruption, is largely human, one of which is education. This change certainly has an impact felt by humans as it is increasingly individualistic and increasingly busy responding to the times. Changes in the world of online education or whatever the government intends to do must certainly accommodate rapid changes in the world that is currently based on information technology. This article uses the type of library research that is a study carried out through data collection related to today's education, data collection or scientific papers that aim to conduct critical and in-depth studies by searching relevant library materials. The results of this study found that students need to be learners who are always hungry for information and become learners who understand and have a variety of approaches such as design thinking (a way of solving problems focused on people centered. Teachers must also have strong scientific competence and have soft skills in the form of critical thinking, creative, communicative, and able to collaborate. n addition it must also be able to spread inspiration for students, be able to be friends with students and of course must be an example.